HUBUNGAN MOTIVASI KERJA DENGAN PERILAKU KESELAMATAN PADA PEKERJA UNIT BONGKAR MUAT PT. X MANUFAKTUR SEMARANG - Nabylla Sharfina Sekar Nurriwanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Safety behavior is a crucial aspect that contributes to reducing the risk of workplace accidents. One of the factors influencing the development of proper safety behavior is work motivation. This study aims to analyze the relationship between work motivation and safety behavior among stevedoring workers at PT. X Manufacturing Semarang. The study population consisted of 47 stevedoring workers, with a sample of 42 respondents selected using a simple random sampling technique. Data analysis was conducted using the chi-square test. The findings revealed a significant association between work motivation and safety behavior (p=0.001; OR=10.5). Based on these results, it is recommended that the company enhance employees’ work motivation by providing rewards, creating a supportive work environment, improving communication, and regularly organizing occupational health and safety programs.